Colombian users' preferences regarding the use of oral contraceptives. A descriptive study (2013)
Combined oral contraceptives have evolved rapidly in recent decades to reduce side effects without affecting the efficacy and according to the preferences of women. It is important to understand the perceptions and expectations of users to improve adherence and reduce the failure of contraception. To this end we conducted a survey-based study within a sample of 389 users aged 18 and 45 years of age in 4 major cities of Colombia, to assess sociodemographic variables in addition to knowledge and preferences of users related to the additional benefits of this contraceptive therapy. The sample consisted mostly of women belonging to middle (62.7%) and high (37.3%) socioeconomic groups. 40.9% of participants were in the group of 18 to 25 years, 43.0% in the group of 26 to 35 years and 16.1% in the group of 36 to 45 years. 58.4% of participants reported knowing at least one additional benefit of oral contraceptives, and when they were asked to rank by importance five attributes proposed by the interviewer as potential beneficial effects was obtained for all age groups the following order: 1) that it does not affect body weight (35.2%), 2) reduction of dysmenorrhea (26.6%), 3) improve the quality of the skin (20.1%), 4) decrease in duration and volume of menstrual bleeding (13.3%) and 5) reduce mood fluctuations (5%). An individualized and comprehensive contraceptive counseling, which assesses the prior knowledge of the potential beneficial effects of oral contraceptives, expectations and preferences of users will contribute to reducing unplanned pregnancy rates associated with incorrect use or with early discontinuation of therapy.